Occupational identity, job satisfaction and their effects on turnover intention among Chinese Paediatricians: a cross-sectional study - Wanjun Deng; Zhichun Feng; Xinying Yao; Tingting Yang; Jun Jiang; Bin Wang; Lan Lin; Wenhao Zhong; Oudong Xia (BMC, 2021)
Abstract Background This study contributes to research on the paediatrician shortage by examining occupational identity, job satisfaction and their effects on turnover intention among paediatricians in China. Methods A multi-stage stratified random sampling method was employed to conduct a questionnaire survey. Of the 4906 survey recipients, valid data were collected from 4198 of the respondents (85.6%). The participants were from seven geographic regions of China (south, central, north, east, northwest, southwest, and northeast). Paediatricians who volunteered and provided written informed consent participated. All variables including basic socio-demographics and work-related characteristics, occupational identity, job satisfaction and turnover intention were based on available literature, and measured on a 5- point Likert scale. Statistical methods such as exploratory factor analysis (EFA), descriptive analysis, common method bias, one-way ANOVA test, Pearson correlation analysis and mediation analysis were used. Results Significant differences were observed among the respondents in terms of turnover intention based on age, education level, marital status, region, the type and grade of practice setting, professional title, years in practise, workload, rest days, and monthly income. Occupational identity and job satisfaction were both negatively related to turnover intention, and occupational identity was positively correlated with job satisfaction (r1 = − 0.601, p < 0.01; r2 = − 0.605, p < 0.01). The results also showed that job satisfaction played a mediating role in the association between occupational identity and turnover intention among Chinese paediatricians. Conclusions Work conditions, workload and salary are crucial factors of turnover intention among paediatricians in China. Therefore, we suggest that healthcare managers should increase investment in paediatrics, implement salary reforms and dedicate more attention to female and young paediatricians, thus reducing turnover intention among Chinese paediatricians.